PTU-059 Burden of liver disease in the west midlands: increased premature mortality. (17th June 2017) - Bhala, N; Haroon, S; Burwood, S; Pennell, C; Carter, H; Daley, A; Day, E; Sharkaway, A El; Ferguson, J; Freshwater, D; Gordon, V; Holt, A; et al.
Abstract : Introduction: Liver disease is a leading cause of premature death in the UK. We sought to assess the public health burden of common liver diseases in the West Midlands by measuring premature mortality. Method: Routine data from Public Health England (PHE) Alcohol and Liver Disease West Midlands Profiles, principally from 2012–16 were assessed. Sources include the Office of National Statistics mortality and population estimates. Specific diseases assessed include: alcoholic liver disease (ALD); non-alcoholic fatty liver disease (NAFLD); chronic viral hepatitis B and C; and hepatocellular cancer (HCC). Results: Premature mortality due to liver disease under 75 years was higher in West Midlands compared to rest of England (19.2 versus 17.8 deaths per 100, 000). This was especially marked in Sandwell, Wolverhampton, Birmingham, Stoke-on-Trent and Dudley. Average annual liver disease deaths also vary by gender, age, and deprivation. Despite a higher proportion of teetotallers (22%–25%), premature mortality of ALD under 75 years was higher than the national average (10.2 versus 8.6 deaths per 100, 000). Premature mortality under 75 years from chronic viral hepatitis related end-stage liver disease/HCC were similar to the national average, and those for mortality under 75 years from NAFLD were lower than the national average. Conclusion: Premature liver mortality under 75 years is significantly higher in the West Midlands compared to the rest of England. A collaborative liver health network in the West Midlands is required to help tackle the burden of preventable liver mortality. References: . Annual Report of the Chief Medical Officer Report on Liver Disease2012 . Lancet Liver Commission Lancet2014 Disclosure of Interest: None Declared